A dimensional approach to functional movement disorders: Heresy or opportunity. (August 2021) - Spagnolo, Primavera A.; Garvey, Marjorie; Hallett, Mark
Highlights: Functional Movement Disorders (FMD) represent a blind spot within psychiatry and have been neglected in neuroscience research. FMD is a disorder of aberrant neurocircuitry interacting with developmental, environmental and genetic factors. Motor and behavioral features of FMD can be mapped into specific functional domains and underlying brain circuits. Adopting a dimensional, neuroscience based framework to FMD is feasible and can critically contribute to uncover disease mechansims. A dimensional assessment of FMD may facilitate the identification of meaningful subtypes of disorder. Abstract: Functional movement disorders (FMD) are a common and disabling neuropsychiatric condition, part of the spectrum of functional neurological/conversion disorder. FMD represent one of the most enigmatic disorders in the history of medicine. However, in the twenty years after the first report of distinctive abnormal brain activity associated with functional motor symptoms, there have been tremendous advances in the pathophysiologic understanding of these disorders. FMD can be characterized as a disorder of aberrant neurocircuitry interacting with environmental and genetic factors. These developments suggest that research on FMD could be better served by an integrative, neuroscience-based approach focused on functional domains and their neurobiological substrates. This approach has been developed in 'Research Domain Criteria' (RDoC) project, which promotes a dimensional approach to psychiatric disorders. Here, we use the RDoC conceptualization to review recent neuroscience research on FMD, focusing on the domains most relevant to these disorders. We discuss how the adoption of a similar integrative framework may facilitate the identification of the mechanisms underlying FMD and could also have potential clinical applicability.